Highly Independent 5G Multiband Antenna using Circular Patch Structure - Adhiyoga, Yohanes Galih; Arifin, Tri Nur; Ilman, Syaeful; Wahyuningsih, Erfiana; Rusdiyanto, Dian; Mahendra, Adhi (Buletin Pos dan Telekomunikasi, 2023)
5G mobile communication technology has attracted much attention in the past three years. However, the development of antennas that can cover three types of 5G bands at once has not been studied. This paper proposes an antenna covering the three frequency bands of 2.3 GHz, 3.5 GHz, and 26 GHz for 5G communication. The proposed antenna uses a microstrip patch design with 50-ohm inset feeding. FDTD mathematical analysis through simulation has been carried out and confirmed that the proposed antenna meets the required specifications in 5G technology. The simulation result shows that the proposed antenna has a good reflection coefficient in the target frequencies of -22.6 dB, -28.26 dB, and -22.48 dB, respectively.